2013
DOI: 10.1371/journal.pone.0066244
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Intracellular Trafficking of Superantigens in Dendritic Cells

Abstract: Bacterial superantigens (SAgs) are exotoxins produced mainly by Staphylococcus aureus and Streptococcus pyogenes that can cause toxic shock syndrome (TSS). According to current paradigm, SAgs interact directly and simultaneously with T cell receptor (TCR) on the T cell and MHC class II (MHC-II) on the antigen-presenting cell (APC), thereby circumventing intracellular processing to trigger T cell activation. Dendritic cells (DCs) are professional APCs that coat nearly all body surfaces and are the most probable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 62 publications
1
18
0
1
Order By: Relevance
“…These data indicate that these antigens induce an enhanced Th1 and pro-inflammatory cytokine response. Antigen presentation by APCs is required for the activation of effector T cells by HBcAg and S. pyogenes [33,34], Previous studies have demonstrated that plasmacytoid DCs are decreased in athletes after running a marathon, and that long-term intensive training may affect the function of innate immune cells, in particular, reducing their capacity to respond to acute challenges, and possibly contributing to an increased risk of infection [35,36]. Moreover, IFN-α and IL-12 derived from DCs play an essential role in Th1 cell differentiation and protecting against pathogen invasion [37].…”
Section: Discussionmentioning
confidence: 99%
“…These data indicate that these antigens induce an enhanced Th1 and pro-inflammatory cytokine response. Antigen presentation by APCs is required for the activation of effector T cells by HBcAg and S. pyogenes [33,34], Previous studies have demonstrated that plasmacytoid DCs are decreased in athletes after running a marathon, and that long-term intensive training may affect the function of innate immune cells, in particular, reducing their capacity to respond to acute challenges, and possibly contributing to an increased risk of infection [35,36]. Moreover, IFN-α and IL-12 derived from DCs play an essential role in Th1 cell differentiation and protecting against pathogen invasion [37].…”
Section: Discussionmentioning
confidence: 99%
“…Each superantigen is specific for a distinct repertoire of V␤ gene products and can therefore activate up to 20% of circulating naive T cells (358). Rampant T-cell activation has also been shown to occur following the uptake of superantigens by dendritic cells in vivo, further contributing to the proinflammatory cascade (359). In addition, in vitro studies suggest that SpeS can induce a strong proinflammatory response from stratified, squamous epithelial cells (225), suggesting a broader role for superantigens in amplifying the host inflammatory response to GAS.…”
Section: Gas Superantigensmentioning
confidence: 99%
“…They are the main source for induction of S. aureus ‐mediated cytokine storm; therefore, SAgs can be a target for therapy against S. aureus infection. There are two pathways for immune stimulation by SAgs; direct stimulation of T cells without DCs by SAgs and DC‐contributed activation of T cells by SAgs . Previous studies have shown that SAgs can directly stimulate T cells without antigen presentation processing by DCs, and is mediated by TCR and MHC class II on T cells, which promotes activation of the V β T cells .…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcal superantigens (SAgs), the potent immune stimulatory exotoxins, induce T-cell activation and proinflammatory cytokine production by directly cross-linking MHC class II on DCs. 12,13 It has been shown that the DCs are important in the presentation of staphylococcal enterotoxins on MHC class II and secrete interleukin-12 (IL-12) for the induction of T helper type 1 and cytotoxic T1 cells immune responses. 1,[13][14][15] Moreover, the depletion of DCs in mice impaired immunity against S. aureus infection.…”
Section: Introductionmentioning
confidence: 99%